THE FORM OF THE COMPLETE SURFACES OF CONSTANT MEAN CURVATURE - Abdel Rahman Abdel Gadir , Abdel Radi; Zaied Elawad Faread, Abdelhalim; AhmedHassan Kubba, Adel; Iesa Mohammed Abker, Mohammed (International Journal For Research In Mathematics And Statistics, 2022)
We explained and classified the complete surfaces of constant mean curvature in addition to construct the first examples of complete surface of positive curvature, properly embedded minimal surfaces and we prove that every complete connected immersed surface with positive extrinsic curvature in must be properly embedded, homeomorphic to a sphere or a plane. We followed the analytical mathematical method and we found that the complete surface of positive curvature has multi applications in different fields of science specially in physics.